Transforming Education in the 21st Century: the Role of Information and Communication Technology in Enhancing Digital Competence - Ghasa Faraasyatul 'Alam; Nurul Faizah (Fahima, 2026)
This study explores the role of Information and Communication Technology (ICT) in enhancing digital competence as a critical element of educational transformation in the 21st century. Digital competence is examined through two main constructs such as Data Information and Knowledge (DIK), and Communication and Collaboration (CC). This research analyzes the impact of ICT on digital competencies, specifically DIK and CC, within the context of 21st century educational transformation. A quantitative approach was employed, utilizing IBM SPSS Statistics 22 and AMOS software for optimal data analysis, including confirmatory factor analysis to accurately identify each variable. The study surveyed 100 respondents, comprising Doctoral and Master's program students from the Faculty of Education, through an online questionnaire. The findings indicate that (a) ICT has a significant positive effect on DIK and (b) ICT positively influences CC. The findings show that ICT use significantly affects the development of digital competence, underscoring the significance of incorporating technology into higher education courses to help learners who are prepared for the future. The implications for education highlight the crucial role of ICT in enhancing the quality of education. Continuous development of ICT is essential for improving the digital competencies of educators, which is vital for successfully navigating the educational transformation of the 21st century.